2015
DOI: 10.1016/j.celrep.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced CDK5 Activation Disrupts Axonal Transport via Lis1/Ndel1/Dynein

Abstract: Summary Axonal transport is essential for neuronal function, and defects in transport are associated with multiple neurodegenerative diseases. Aberrant cyclin dependent kinase 5 (CDK5) activity, driven by the stress-induced activator p25, is also observed in these diseases. Here, we show that elevated CDK5 activity increases the frequency of nonprocessive events for a range of organelles including lysosomes, autophagosomes, mitochondria, and signaling endosomes. Transport disruption induced by aberrant CDK5 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 51 publications
7
82
1
Order By: Relevance
“…In this study, expression of kinase-dead Cdk5 did not affect the axonal transport of lysosomes, mitochondria, or TrkB-containing endosomes [75], suggesting that Cdk5 does not play a role in the regulation of axonal transport under normal conditions. By contrast, increasing Cdk5 activity disrupted the axonal transport of these cargoes [75], suggesting that Cdk5 modulates axonal transport only under cellular stress. Although the reason for these conflicting results is unclear, it may be related to differences in the protocol used for DRG isolation and maintenance [72,75].…”
Section: Jnkscontrasting
confidence: 46%
See 1 more Smart Citation
“…In this study, expression of kinase-dead Cdk5 did not affect the axonal transport of lysosomes, mitochondria, or TrkB-containing endosomes [75], suggesting that Cdk5 does not play a role in the regulation of axonal transport under normal conditions. By contrast, increasing Cdk5 activity disrupted the axonal transport of these cargoes [75], suggesting that Cdk5 modulates axonal transport only under cellular stress. Although the reason for these conflicting results is unclear, it may be related to differences in the protocol used for DRG isolation and maintenance [72,75].…”
Section: Jnkscontrasting
confidence: 46%
“…By contrast, increasing Cdk5 activity disrupted the axonal transport of these cargoes [75], suggesting that Cdk5 modulates axonal transport only under cellular stress. Although the reason for these conflicting results is unclear, it may be related to differences in the protocol used for DRG isolation and maintenance [72,75].…”
Section: Jnksmentioning
confidence: 97%
“…CDK5 has many known functions in neurons, including dendritic development, 20 neuronal migration, 21 axonal guidance, 22 and organelle transport. 2327 Previous work has shown that CDK5 activates dynein indirectly, through phosphorylation of Ndel1, which controls dynein activity in conjunction with the dynein-binding protein Lis1. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of Ndel1 by CDK5 results in the formation of a phospho-Ndel1/Lis1 complex 27 ; the binding of Lis1 to the dynein motor domain within this complex results in steric blockade of the dynein powerstroke. 28 This leaves dynein unable to release from the microtubule even when ATP is bound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation